Molecular level insight on the adsorption of carboxylic acids to oxide nanoparticles in aqueous solution by X-ray photoelectron spectroscopy. Issue 58 (28th January 2016) - Olivieri, Giorgia; Goel, Alok; Brown, Matthew A.
Abstract : X-ray photoelectron spectroscopy (XPS) from a liquid microjet is used to follow a chemical reaction at the aqueous-nanoparticle interface. Abstract : We show, for the first time, the ability to follow the surface chemistry (acid–base equilibrium) of a colloid nanoparticle (Al x O y @SiO2 ) while simultaneously monitoring the adsorption of a solute molecule (HCOOH) from solution using in situ X-ray photoelectron spectroscopy. Based on the results of the Al 2p and C 1s spectra a mechanism is proposed.